Multicellular String-Like Structure Formation by Salmonella Typhimurium Depends on Cellulose Production: Roles of Diguanylate Cyclases, YedQ and YfiN - Varghese, Alan; Ray, Semanti; Verma, Taru; Nandi, Dipankar (Frontiers in Microbiology, 2020)
Bacteria face diverse stresses in the environment and, sometimes, respond by forming multi-cellular structures, e.g. biofilms. Here, we report a novel macroscopic and multi-cellular structure formed by Salmonella Typhimurium, which resembles small strings. These string-like structures, ~1 cm long, are induced under some stress conditions: iron deprivation by 2,2-Bipyridyl or low amounts of antibiotics or ethanol in minimal media. However, cells in strings revert back to planktonic growth upon return to nutrient rich media. Compared to planktonic cells, strings are more resistant to antibiotics and oxidative stress. Also, strains lacking csgD or rpoS, which are defective in the classical rdar biofilm formation, form strings. Furthermore, some biofilm inducing conditions do not result in strings and vice-versa, demonstrating that strings are not related to classical CsgD-dependent biofilms. Cells in a string are held together by cellulose and a strain lacking bcsA, which is defective in cellulose production, does not form strings. In addition, reductive stress conditions such as dithiothreitol (DTT) or mutations in the Disulfide bonding system (DSB) also give rise to strings. The amounts of c-di-GMP are increased upon string formation and studies with single and double deletion strains of the diguanylate cyclases, yedQ (STM1987) primarily and yfiN (STM2672) partly, revealed their importance for string formation. This is the first study showcasing the ability of Salmonella to produce high amounts of cellulose in liquid culture, instead of an interface, in a CsgD-independent manner. The relevance and possible applications of strings in the production of bacterial cellulose and bioremediation are discussed.